Attitudes towards female genital cutting among adolescents in rural Burkina Faso: a multilevel analysis - Greis, Alina; Bärnighausen, Till; Bountogo, Mamadou; Ouermi, Lucienne; Sié, Ali; Harling, Guy (Tropical medicine & international health, 2020)
Objective Despite decades of abandonment efforts, female genital cutting (FGC) prevalence rates in Burkina Faso remain high. We present updated prevalence data from rural adolescents and examine factors associated with FGC receipt and attitudes, testing predictions of social convention and modernisation theory regarding the abandonment process. Methods We interviewed 1644 adolescents aged 12-20 years from 10 villages and one sector of Nouna town in the Nouna Health and Demographic Surveillance site in late 2017. Response-weighted prevalence for self-reported FGC receipt, beliefs about religious requirements, and attitudes about abandonment were calculated. We used bivariate regression and two-level hierarchical models to test whether social convention or modernisation theory-related factors predicted current FGC attitudes. Results 43% of women in our sample reported having undergone FGC; 74% of women and 76% of men believed FGC should be abandoned. The strongest predictors of FGC receipt were religion, ethnicity, the village’s FGC rate and mother’s education. The strongest predictors of FGC abandonment attitudes were religion, ethnicity, belief that FGC is religiously required, and own FGC status. Males’ attitudes were less determined by community factors than females’; females’ attitudes were more strongly influenced by factors linked to modernization, such as maternal education and household wealth. Conclusions FGC continues to be common in rural and small-town Burkina Faso, and our analysis suggests that social conventions play an important role in its continuation. However, modernisation-related factors were stronger predictors of abandonment attitudes than of FGC status, particularly in adolescent women. The changes these relationships suggest may benefit the next generation of girls.